Analisis Keberlanjutan Dimensi Sosial Budaya Usahatani Padi Sawah di Kabupaten Siak Provinsi Riau - Rachmiwati Yusuf; Usman Pato; Usman M Tang; Rahman Karnila Karnila (Dinamika Lingkungan Indonesia, 2019)
The study was conducted from January to July 2018 in four sub-districts (Bunga Raya, Sabak Auh, Sungai Apit and Sungai Mandau) in Siak Regency. The sample of farmers in this study were 203 people who were selected by purposive sampling. Data collection was done by interviewing techniques using questionnaires and field observations. The analysis of the sustainability of lowland rice farming was carried out based on the assessment of index and sustainability status using the Rap-Rice method in Multi-Dimensional Scaling (MDS). The purpose of this study was to analyze the index and the status of sustainability of the socio-cultural dimensions of wetland farming and analyze the role of each of the socio-cultural attributes that have sensitivity to the management of rice farming in the future. The results of Rap-Rice analysis of the seven socio-cultural attributes analyzed, two attributes provide sensitivity to the District (Bunga Raya, Sabak Auh and Sungai Mandau). Four attributes give sensitivity to Sungai Apit District. The attribute that gives sensitivity to all sub-districts is the attribute of attending training / counseling. Based on socio-cultural conditions, the analysis of wetland rice farming in Siak District showed a fairly sustainable category for Bunga Raya District (56.7%), Sabak Auh (50.80%) and Sungai Mandau (51.10%) while for Sungai Apit Subdistrict the value was obtained (47.70%) or less sustainable .